Two new species of Fauveliopsidae (Annelida, Sedentaria) from submarine caves and deep sea, Japan - Jimi, Naoto; Fujimoto, Shinta; Ogawa, Akito; Fujita, Yoshihisa; Shigenobu, Yuya; Imura, Satoshi (Zootaxa, 2020)
Two new species of fauveliopsid annelids, Fauveliopsis antri sp. nov. and Laubieriopsis soyoae sp. nov., are described based on specimens collected from Japanese waters. Fauveliopsis antri sp. nov. inhabits submarine caves and can be discriminated from the other congeners by the following features: i) 32 chaetigers, ii) chaetigers 1–3 with stout hooks, iii) minute body (about 1 mm in length), iv) all parapodia with same number of chaetae (2 notochaetae; 2 neurochaetae), and v) presence of dorsal and ventral papillae. Laubieriopsis soyoae sp. nov. inhabits deep water sediments and can be distinguished from the other congeners by: i) 24 chaetigers, ii) chaetigers 1–3 without annulations, and iii) acicular chaetae with tips entire, without denticles.